Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 2 - Mid-Chapter Check Point: 16

Answer

m=-$\frac{6}{5}$

Work Step by Step

$\frac{3(m+2)}{4}$=2m+3 $\frac{4[3(m+2)]}{4}$=4(2m+3) 3(m+2=4(2m)+4(3) 3(m)+3(2)=8m+12 3m+6=8m+12 3m+6-12=8m 3m-6=8m -6=8m-3m -6=5m $\frac{-6}{5}$=m m=-$\frac{6}{5}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.